ВПЛИВ ВИСОКОЧАСТОТНИХ ВТРАТ РЕАЛЬНОГО КОНДЕНСАТОРА ПРИ ЗАСТОСУВАННІ БЕЗФІЛЬТРОВОГО МЕТОДУ ЗМЕНШЕННЯ НЕСИМЕТРИЧНИХ КОНДУКТИВНИХ ЗАВАД ВІД ТРАНЗИСТОРНИХ ПЕРЕТВОРЮВАЧІВ ІЗ НАКОПИЧУВАЛЬНИМ ДРОСЕЛЕМ - Гурін, В.К.; Павловський, В.О.; Юрченко, О.М. (Інститут електродинаміки НАН України, Київ, 2019)
In this paper, a further analysis of a non-traditional method of common-mode (CM) noise decreasing for transistor converters with accumulating choke is described. It is obtained an expression for the capacitance of a real capacitor having high frequency losses in compensating circuit which provides maximal decreasing of CM noise. The correctness ofthe obtained expression was checked and confirmed with the aid of PSPICE. The dependence of effective CM noise decreasing on mentioned above losses of the real capacitor also was showed in the paper. References 3, figures 3.